The Online Journal Aggregator System Design Using User Centered Design (UCD) Approach - Afrianto, Irawan; Atin, Sufa; Heryandi, Andri; Warlina, Lia (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 3 December 2018, 2018)
Journal as a medium to explain the results of research. It has developed in such a way especially because of the rapid support of information and communication technology today. Various models of online-based journaling management can be easily operated by journals managers as well as writers / researchers who will include research results in the journal. It's just that with the number of journals that exist today, causing difficulties for the manager of journals to be able to promote the journals he managed, in addition to the manager of the journal sometimes difficult to get a researcher who would put his paper into the journal he manages. Meanwhile, with the number of journals that have been online, researchers will find it difficult to get information from the journals. Researchers should open their journal entries, read their profiles and publications, until they are interested to include papers in the journal. This problem is the background of the development of online journals aggregator system, which with this system will facilitate the meeting between journals, journal managers and writers or researchers. In order to develop an online journal aggregator system, a software development method is needed that directly captures the needs of its users. This study aims to implement the UCD method in the functional design and interface of the aggregator journal system. In order to determine the level of acceptance and support of prospective users of the aggregator journal system. Measurements were taken using Likert method with user acceptance preferences for 3 aspects of the system, namely: accessibility, navigation, and content aspects. The measurement results show 82% of prospective users state that the functional design and interface of the aggregator journal system can be accepted and can be developed to the next stage.